Evaluación de la dispersión de pigmento en resinas acrílicas para la fabricación de dientes artificiales (2010)
ABSTRACT: In the first stage of manufacture of artificial teeth, pigments are dispersed in a dry powder composed of fine spherical particles of acrylic resin. This dispersion has different characteristics to the usual dispersion of pigments in liquid resins of paints and coatings, or in the manufacture of plastics. There is a lack of reports on methods of analysis and control of such processes. This article aims to evaluate the method of tinting power, usual in industrial coatings, contrasting the results with the percentage of adhered pigment to the surface of resin by analyzing SEM photographs with digital image processing (DIP) techniques. Three alternative methods based on analysis of the reflectance curves are proposed and discussed. These three methods enable a quicker assessment of the dispersion process than the former ones, and even allow to determine the value of the pigment band gap energy. The tinting power method proves to be the most sensitive to differences in dispersion. Finally, the four methods are applied. Comparison among three milling processes with different collision energies are presented together with their limitations.